(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Head and neck tissue sarcoma are rare with potential high morbidity and mortality. The purpose of the present study was to present these cases and determine the optimal treatment for adult patients with head and neck soft tissue sarcomas. Methods: It is a retrospective study of adult head and neck soft tissue sarcoma conducted in the Department of Otorhinolaryngology at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) which is one of the national referral center within the period of 16 years from 1998 till 2014. Results: Fourteen cases were reviewed in which7 histopathological variations of soft tissue sarcomas were identified. Local control after surgery alone or combined with radiotherapy was obtained in 50 % of the patients which is influenced by histologic grade, tumor size, and surgical margins. Patients with high-grade tumors or positive margins have improved local control if adjuvant radiotherapy is used. Distant metastases occurred in 14.2 % of patients and the 5-year survival rate was 50 %. Conclusions: The optimal treatment for adult head and neck soft tissue sarcomas is surgery. Adjuvant radiotherapy improves outcomes for those with high-grade tumors or positive margins. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.69-76